The automotive industry: when regulated supply fails to meet demand. The case of Italy - Antonio Sileo; Monica Bonacina (Fondazione Eni Enrico Mattei (FEEM), 2024)
This article studies the effects of the latest European regulations on carbon emissions on the Italian car market and discusses the possibility of achieving climate neutrality of road transport through the "mere" replacement of cars currently on the road with new zeroemission cars. Since 2016, au-tomakers' production strategies have changed dramatically, with an increasing number of zero (and low) emission models on car lists. To date, these changes on the supply side have not been matched by similar changes in purchasing habits. In recent years, not only have few zero (and low) emission cars been sold, but also few new cars. Unless epoch-making changes occur, it is com-pletely unrealistic to think that we can achieve climate neutrality by 2050 by leveraging exclusively on the renewal of the fleet.
Keywords: L62; Q55; Q58; R41; 330; automotive market; sustainable mobility; road transport decarbonization; electro-mobility; EU-car CO2 regulation